SULFUR TRIOXIDE DECOMPOSITION CATALYST, SULFUR DIOXIDE PRODUCTION PROCESS USING SULFUR TRIOXIDE DECOMPOSITION CATALYST, HYDROGEN PRODUCTION PROCESS USING SULFUR DIOXIDE PRODUCTION PROCESS, AND PROCESS FOR PRODUCING SULFUR TRIOXIDE DECOMPOSITION CATALYST - TAKESHIMA, SHINICHI; MACHIDA, MASATO (2015)
A sulfur trioxide decomposition catalyst includes: a composite oxide containing an alkali metal and vanadium; and a catalyst support on which the composite oxide is supported. In addition, a process for producing a sulfur trioxide decomposition catalyst includes: impregnating the catalyst support with one solution of a solution containing an alkali metal compound and a solution containing a vanadium compound, and drying and preliminarily calcining the catalyst support; and impregnating the preliminarily calcined catalyst support with the other solution of the solution containing the alkali metal compound and the solution containing the vanadium compound, and drying and calcining the catalyst support. L'invention concerne un catalyseur de décomposition de trioxyde de soufre comprenant : un oxyde composite contenant un métal alcalin et du vanadium ; et un support de catalyseur supportant l'oxyde composite. Le procédé de production du catalyseur de décomposition de trioxyde de soufre consiste à imprégner le support de catalyseur d'une solution contenant un composé de métal alcalin et d'une solution contenant un composé de vanadium, et à sécher et calciner préalablement le support de catalyseur ; et à imprégner le support de catalyseur préalablement calciné d'une autre solution contenant le composé de métal alcalin et de la solution contenant le composé de vanadium, et à le sécher et le calciner.